Exploring the link between C iv outflow kinematics and sublimation-temperature dust in quasars. Issue 2 (14th December 2020) - Temple, Matthew J; Banerji, Manda; Hewett, Paul C; Rankine, Amy L; Richards, Gordon T
ABSTRACT: Using data from SDSS, UKIDSS, and WISE, we investigate the properties of the high-frequency cutoff to the infrared emission in ≃5000 carefully selected luminous ( L bol ∼ 10 47 ) type 1 quasars. The strength of ≃2  μ m emission, corresponding to emission from the hottest ($T\gt 1200\rm \, K$ ) dust in the sublimation zone surrounding the central continuum source, is observed to correlate with the blueshift of the C iv λ1550 emission line. We therefore find that objects with stronger signatures of nuclear outflows tend to have a larger covering fraction of sublimation-temperature dust. When controlling for the observed outflow strength, the hot dust covering fraction does not vary significantly across our sample as a function of luminosity, black hole mass, or Eddington fraction. The correlation between the hot dust and the C iv line blueshifts, together with the lack of correlation between the hot dust and other parameters, therefore provides evidence of a link between the properties of the broad emission line region and the infrared-emitting dusty regions in quasars.